MEKANISME DAN PROSEDUR PEMBUKAAN RAHASIA BANK - Bambang Catur SP (SALAM: Jurnal Sosial dan Budaya Syar-i, 2014)
Abstract: Mechanisms and procedures at the Opening of Bank Secrecy. The bank secrecy is the right of customer, which must be maintained by the bank. Bank Secrecy is all things related to the storage of information about customers and their savings. However, there are some provisions that allow for the bank to open a secret bank customers, with the for the benefit of the State and society, the purpose of taxation, national trade interests, the interests of the criminal and civil justice, the importance of banking activities, and all set in legislation. Keywords: Bank, Bank Secrecy, Opening Procedures Abstrak: Mekanisme dan Prosedur Pembukaan Rahasia Bank. Pada dasarnya rahasia bank merupakan hak nasabah yang harus dijaga oleh pihak bank. Rahasia Bank adalah segala sesuatu yang berhubungan dengan keterangan mengenai nasabah penyimpanan dan simpanannya. Akan tetapi ada beberapa ketentuan yang membolehkan bagi pihak bank untuk membuka rahasia bank nasabahnya, dengan ketentuan untuk kepentingan Negara dan masyarakat luas, untuk kepentingan perpajakan, untuk kepentingan piutang negara, untuk kepentingan peradilan pidana dan perdata, untuk kepentingan kegiatan perbankan, dan semuanya diatur dalam peraturan perundang-undangan. Kata Kunci: Bank, Rahasia Bank, Prosedur PembukaanDOI:10.15408/sjsbs.v1i1.1525